Adapting Curriculum and Materials for Distance Learning: Strategies for Effective Distance Education - Shandi Septian Prastiyo; Velienchia Oktha Navisha (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research addresses the importance of adapting distance learning curricula and materials to develop effective and appropriate teaching strategies to meet the diverse needs of students. In a learning context where there is an increasing reliance on technology and limited face-to-face interaction, to ensure that the learning process is inclusive, flexible and meets the expected quality standards of education, curriculum adaptation is essential. This research aims to identify and develop strategies to improve the effectiveness and quality of distance learning, focusing on student engagement, motivation and active participation in the learning process. This research uses a case study approach to analyze the different curriculum adaptation methods used in online and offline learning. These methods include the appropriate utilization of digital technology, the application of interactive learning approaches, and the design of educational materials that are easily accessible and comprehensible to students from various backgrounds. Research shows that such adaptive strategies increase student engagement, material comprehension and learning satisfaction. In summary, adapting PJJ curriculum and materials not only improves learning effectiveness, but also plays an important role in fostering student independence and is essential in meeting the challenges of education in today's digital era.